THE PROCESS OF COMMUNITY EMPOWERMENT IN INTEGRATED WASTE MANAGEMENT IN THE PEDURUNGAN KIDUL VILLAGE SEMARANG CITY - Anggraini, Fitri Febrina; Djumiarti, Titik (Journal of Public Policy and Management Review, 2020)
ABSTRACT Integrated waste management in Pedurungan Kidul Village is an activity of community empowerment process in an effort to make waste management run optimally. This study aims to identify and analyze the process of community empowerment in integrated waste management in the Pedurungan Kidul Village, Semarang City. The research method used is a qualitative approach with technical taxonomic analysis. The data collection techniques are by observation, interview and documentation. The results showed that the process of community empowerment in integrated waste management in the Pedurungan Kidul Kelurahan of Semarang City through 3 processes that must be carried out include Awareness, Capacitance and Empowerment. Awareness Stage is by doing motivation. Where motivation activities in awareness activities are carried out by way of socializing, deliberation and coaching the importance of managing waste that can be of sale value. Then the capacity building step is done through mentoring. Guidance activities are carried out through training in utilization of organic and inorganic waste processing. Then the final process in empowerment is done by Enrichment, where the empowerment is done through a facilitator by providing resource assistance to actively participate in making handicrafts processed inorganic and organic waste. However, in the process of community empowerment in integrated waste management in the Semarang City Pedurungan Kidul Village there are still obstacles encountered in the process of awareness and capacity building, where the constraint in the awareness process is the lack of socialization regarding awareness of clean and healthy living. Then the obstacle in the capacity building stage is the lack of role of the Department of the Environment in providing training in waste management. The advice that can be given is to increase awareness about clean and healthy living awareness in waste disposal behavior and waste management and the local government is expected to further enhance its role and coordinate with other stakeholders.